Step
*
of Lemma
fun-path-member-connected
∀[T:Type]. ∀f:T ⟶ T. ∀L:T List. ∀x,y:T.  ∀a:T. ((a ∈ L) 
⇒ {x is f*(a) ∧ a is f*(y)}) supposing x=f*(y) via L
BY
{ xxx(RepeatFor 2 ((D 0 THENA Auto))
      THEN Assert ⌜∀L:T List. ∀x,y:T.  (x ∈ L) ∧ (∀a:T. ((a ∈ L) 
⇒ {x is f*(a) ∧ a is f*(y)})) supposing x=f*(y) via L⌝
           ⋅
      )xxx }
1
.....assertion..... 
1. [T] : Type
2. f : T ⟶ T
⊢ ∀L:T List. ∀x,y:T.  (x ∈ L) ∧ (∀a:T. ((a ∈ L) 
⇒ {x is f*(a) ∧ a is f*(y)})) supposing x=f*(y) via L
2
1. [T] : Type
2. f : T ⟶ T
3. ∀L:T List. ∀x,y:T.  (x ∈ L) ∧ (∀a:T. ((a ∈ L) 
⇒ {x is f*(a) ∧ a is f*(y)})) supposing x=f*(y) via L
⊢ ∀L:T List. ∀x,y:T.  ∀a:T. ((a ∈ L) 
⇒ {x is f*(a) ∧ a is f*(y)}) supposing x=f*(y) via L
Latex:
Latex:
\mforall{}[T:Type]
    \mforall{}f:T  {}\mrightarrow{}  T.  \mforall{}L:T  List.  \mforall{}x,y:T.
        \mforall{}a:T.  ((a  \mmember{}  L)  {}\mRightarrow{}  \{x  is  f*(a)  \mwedge{}  a  is  f*(y)\})  supposing  x=f*(y)  via  L
By
Latex:
xxx(RepeatFor  2  ((D  0  THENA  Auto))
        THEN  Assert  \mkleeneopen{}\mforall{}L:T  List.  \mforall{}x,y:T.
                                      (x  \mmember{}  L)  \mwedge{}  (\mforall{}a:T.  ((a  \mmember{}  L)  {}\mRightarrow{}  \{x  is  f*(a)  \mwedge{}  a  is  f*(y)\}))  supposing  x=f*(y)  via  L\mkleeneclose{}
                  \mcdot{}
        )xxx
Home
Index